CLINICAL AND EXPERIMENTAL STUDY OF ROTARY NICKEL TITANIUM ENDODONTIC INSTRUMENTS - A. A. Adamchik; F. M. Laypanova (Кубанский научный медицинский вестник, 2016)
A wide range of rotating nickel-titanium instruments on the dental market where manufacturers provide only exemplary resource mechanical tools conventionally dividing them into reusable and disposable, thus, does not give advice on operation time and clinical recommendations depending on system complexity root canal, cry a lot of questions. The paper discusses the results of experimental and clinical research cycle fatigue machine endodontic NiTi instruments. Dental phantom «Model for determining the fatigue strength of mechanical endodontic instruments in root canal preparation of teeth» to determine the cyclic durability of mechanical endodontic instruments reasonably choose endodontic nickel-titanium instruments of a certain size and taper depending on the angle of the root canal bending teeth in the clinic, thereby warning possible tool breakage risks in the processing of root canal during treatment.